Analysis of the Standard of Living of the Population of The Republic of Uzbekistan (Eurasian Research Bulletin, 2022)
In the article, studying various studies of the influence of the service sector on the gross regional product of the Fergana region, the share of the service sector in GRP was studied. The data showed that the main share of the service sector was 64.00% in 2010, which is a high figure compared to the following years. The lowest rates are 45.67% and 46.5% in 2015-2016. The analysis using a distributed lag, using the example of the Fergana region, showed which years had a positive and negative impact on the gross regional product and what needs to be done for the government through the digitalization of the economy. The author analyses the structure of the service sector for 11 years and proposes some measures for the optimal solution of problems with a microeconomic policy in the example of the Fergana region